Analisis Pengunaan Media Digital Terhadap Perkembangan Bahasa Anak Usia Dini - Lidiana Nasur (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to analyze the influence of digital media use on early childhood language development. The research employed a Systematic Literature Review (SLR) method by examining various scientific journals, articles, and books related to digital media in early childhood learning. Data were analyzed qualitatively through identification, classification, and interpretation of relevant findings concerning the positive and negative impacts of digital media on children’s language development. The findings indicate that appropriate and supervised digital media use can improve children’s vocabulary, listening skills, communication abilities, and learning motivation through interactive audio-visual content. However, excessive use without parental supervision may reduce social interaction, increase gadget dependency, and hinder language and emotional development. The novelty of this study lies in its emphasis on the balance between the educational benefits and risks of digital media exposure in early childhood language acquisition. The study implies that parents and educators play an essential role in selecting educational content and regulating screen time to optimize children’s language development.